A Topsoil Salinity Observatory for Arable Lands in Coastal Southwest Bangladesh - Showmitra Kumar Sarkar; Mafrid Haydar; Rhyme Rubayet Rudra; Tanmoy Mazumder; Md. Sadmin Nur; Md. Shahriar Islam; Shakib Mohammad Sany; Tanzim Al Noor; Shakil Ahmed; Myisha Ahmad; Annajmus Sakib; Sai Ravela (Scientific Data)
Abstract The research assesses soil salinity in the southwest coastal region of Bangladesh, collecting a total of 162 topsoil samples between March 1 and March 9, 2024, and processing them following the standard operating procedure for soil electrical conductivity (soil/water, 1:5). Electrical conductivity (EC) measurements obtained using a HI-6321 advanced conductivity benchtop meter were visualized spatially using bubble density mapping. The map demonstrates that soil salinity in the region of interest ranges from 0.05 to 9.09 mS/cm. This dataset provides a critical resource for soil salinity-related research in the region, offering valuable insights to support decision-makers in understanding and mitigating the impacts of soil salinity in Bangladesh’s coastal areas.